Characteristics and control of the 24‐hour ambulatory blood pressure in patients with metabolic syndrome. Issue 3 (25th February 2021) - Huang, Jian‐Feng; Li, Yan; Shin, Jinho; Chia, Yook‐Chin; Sukonthasarn, Apichard; Turana, Yuda; Chen, Chen‐Huan; Cheng, Hao‐Min; Ann Soenarta, Arieska; Tay, Jam Chin; Wang, Tzung‐Dau; Kario, Kazuomi; et al.
Abstract: Asian countries are facing an increasing prevalence of metabolic syndrome (MetS), which may aggravate the burden of cardiovascular diseases in this region. MetS is closely associated with ambulatory blood pressure (BP). Patients with MetS, compared to those without, had a twofold higher risk of new‐onset office, home, or ambulatory hypertension. Furthermore, the risk of new‐onset MetS in patients with white‐coat, masked and sustained hypertension was also doubled compared to normotensives. High‐risk masked hypertension and blunted nighttime BP dipping are common in patients with MetS, suggesting perfect 24‐hour BP control with long‐acting antihypertensive drugs and early initiation of combination therapy might be especially important for patients with MetS.